Examining Legislation and Enforcement Mechanisms to Combat International Human Trafficking from an Islamic Criminal Law Perspective - Nameer Hashim Qasim; Said Salih Mohammed; Raad Fajer Ftayh; Mohammed Zuhair; Jassim Kadhi Kabrch (Institut Agama Islam Negeri Curup, 2025)
This study aims to uncover the potential use of Islamic criminal law to strengthen anti-trafficking responses, assessing and evaluating the adequacy of existing legal responses. Human trafficking continues to be an alarming international problem, with global legal mechanisms not always ensuring effective law enforcement and victim protection. Even with national treaties and laws in place, differences in prosecution rates and lack of legal structures keep trafficking networks running. This study employs a mixed-methods approach by integrating legal analysis along with qualitative insights from both legal practitioners and trafficking survivors to highlight enforcement faults. It researches Fasad fil Arz (corruption on earth) versus Hadd (fixed punishments) principles and their capacity to improve deterrence and accountability. Through this research, we see how the rational and punitive nature of secular legal systems is balanced by Islamic criminal heritage by presenting the ideological, moralistic, and rehabilitation nature of Islamic law. The article recommends a hybrid legal model that integrates local Islamic principles and international standards to address enforcement inconsistencies and enhance protection for victims. It contends that the incorporation of Islamic legal mechanisms, such as the introduction of restitution and community-based regulation, can help address existing gaps in prosecution and survivors’ rehabilitation. It further emphasizes the need for cross-jurisdictional cooperation, legislative reform and strengthened institutional capacity for the effective countering of trafficking. This study thus adds to wider debates on how to strengthen anti-trafficking strategies through a holistic approach that brings together secular and Islamic legal traditions by calling for a more holistic legal framework. Also, underscores the necessity of integrating Islamic legal principles with international cooperation to create a robust and effective anti-trafficking strategy.